AAPM WGTG51 Report 374: Guidance for TG‐51 reference dosimetry. Issue 11 (19th September 2022) - Muir, Bryan; Culberson, Wesley; Davis, Stephen; Kim, Grace Gwe‐Ya; Lee, Sung‐Woo; Lowenstein, Jessica; Renaud, James; Sarfehnia, Arman; Siebers, Jeffrey; Tantôt, Laurent; Tolani, Naresh
Abstract: Practical guidelines that are not explicit in the TG‐51 protocol and its Addendum for photon beam dosimetry are presented for the implementation of the TG‐51 protocol for reference dosimetry of external high‐energy photon and electron beams. These guidelines pertain to: (i) measurement of depth‐ionization curves required to obtain beam quality specifiers for the selection of beam quality conversion factors, (ii) considerations for the dosimetry system and specifications of a reference‐class ionization chamber, (iii) commissioning a dosimetry system and frequency of measurements, (iv) positioning/aligning the water tank and ionization chamber for depth ionization and reference dose measurements, (v) requirements for ancillary equipment needed to measure charge (triaxial cables and electrometers) and to correct for environmental conditions, and (vi) translation from dose at the reference depth to that at the depth required by the treatment planning system. Procedures are identified to achieve the most accurate results (errors up to 8% have been observed) and, where applicable, a commonly used simplified procedure is described and the impact on reference dosimetry measurements is discussed so that the medical physicist can be informed on where to allocate resources.